Assessing salivary cortisol and testosterone as non-invasive biomarkers for GnRH-immunocastration efficiency in heavy pigs - E. Atallah; G. Pesenti Rossi; J. F. Soares Filipe; E. Dalla Costa; S. M. Mazzola; M. Minero; A. Pecile; A. Motta; S. Barbieri (BMC Veterinary Research)
Abstract Background Efforts to enhance animal welfare have led to the investigation of alternative methods of performing surgical castration on young pigs that induce stress and anxiety. This study was conducted to establish the efficacy of immunocastration in heavy pigs, with non-invasive diagnostic indicators being salivary cortisol and testosterone levels. Results At 225 days, a significant difference was noted in the cortisol levels of pigs in the treatment groups, with the immune-castrated (IC) recording higher levels than the surgically castrated (SC) animals. Furthermore, 196-day and 225-day-old IC pigs had remarkably elevated testosterone amounts. The changes that were seen to be significant after immunocastration indicate that the use of salivary tests can be a good way of evaluating how effective this alternative method is. Among SC pigs, a significant positive relationship was found between salivary cortisol and salivary testosterone concentrations at 225, 240, and 268 days. Moreover, no association was observed in IC animals. These findings signal that the hormonal levels and their interactions are related to different physiological reactions of pigs to immunological and surgical castration. Conclusions The results underline the significance of salivary cortisol and testosterone as stress and hormonal balance indicators in heavy pigs with immunocastration. This study provides insights into the complex hormonal reactions to stress post-castration and emphasizes the need for further research to enhance animal welfare practices. Overall, salivary testing offers a practical approach to evaluating immunocastration efficacy and monitoring pig health and well-being.